THE CORRELATION BETWEEN STUDENTS’ LEARNING STYLES AND STUDENTS’ ENGLISH LINGUISTIC INTELLIGENCE - Tri Indah Rezeki; Rakhmat Wahyudin Sagala; Rabukit Damanik (STKIP Budidaya Binjai, 2018)
Learning style is the key to develop processes in working, learning at school, and interaction social with people. Each students has different learning style types and it influences students’ English linguistic intelligence forming. The aim of this study is to find out kinds of learning styles and the correlation to their linguistic intelligence at Eleventh grade students of SMA Negeri 1 Binjai Kab. Langkat. This study was correlation research that used to know whether there was a correlation between learning styles and English linguistic intelligence at Eleventh grade students of SMA Negeri 1 Binjai Kab. Langkat. This study was done by taking 50 respondents at Eleventh grade students of SMA Negeri 1 Binjai Kab. Langkat that had English linguistic intelligence based on random sampling. The collecting of data in this study used questioner method. The technique of data analysis in this study used correlation product moment. The result of study showed that rhitung from correlation between learning styles (Visual, Auditory, and Kinesthetic) and English linguistic intelligence were bigger than rtabel (0.564, 0.656, 0.495) to N=50 by its sig 0% with the result that H0 was refused and Ha was accepted that had mean there was a significant correlation between learning styles and English linguistic intelligence at Eleventh grade students of SMA Negeri 1 Binjai Kab. Langkat. The result showed the students had varieties frequencies of English linguistic intelligence because it was appropriate by learning styles that they had. It can be concluded there is a correlation between learning styles and English linguistic intelligence at Eleventh grade students of SMA N 1 Binjai Kab. Langkat. Keywords: Learning Styles, English Linguistic Intelligence